A novel normal parameter reduction algorithm of soft sets - Ma, Xiuqin; Norrozila, Sulaiman; Qin, Hongwu; Herawan, Tutut (Springer Nature, 2010)
In this paper, we propose a novel normal parameter reduction algorithm of soft sets based on the oriented-parameter sum, which can be carried out without parameter important degree and decision partition. We present some new related definitions and proved theorems of normal parameter reduction. The comparison result on a Boolean-valued dataset shows that, the proposed algorithm involves relatively less computation and is easier to implement and understand as compared with the soft set-based algorithm of normal parameter reduction.